Historical understanding as means to strengthen students’ national integration in Papua - Hasirun, La Ode; Aqil, Muhammad; Loppies, Megiridha (Jurnal Teori dan Praksis Pembelajaran IPS, 2026)
One of the important issues in a multicultural society is national integration, marked by its historical and ethnic diversity. Education is one of the strategic forums in developing social cohesion, identity, and inclusive citizenship in today's young generation. Through a mixed method with a sequential description design, this study aims to find out how students' understanding of science and history is related to the attitude of national integration in Papua. Quantitative data on the understanding of local and national science and history concepts, and integrative attitudes were obtained through structured questionnaires on high school students. Meanwhile, qualitative data on students' sense of national togetherness was obtained through observation of teachers' teaching practices in the classroom. Results indicated that students generally had a good understanding of science and history and moderate integrative attitudes. Pearson correlation analysis revealed a moderate relationship between science understanding and integration attitudes, while the relationship with history understanding was strong. Regression analysis further showed that students’ understanding of science and history contributed substantially to the development of national integration attitudes. Qualitative findings suggest that contextual learning strengthens integrative values. Science lessons incorporated local ecosystem examples, whereas history lessons emphasized the contributions of Papuan figures to national development. These findings highlight the importance of contextual and interdisciplinary learning approaches to enhance students’ national integration attitudes in culturally diverse settings.